Case report: Extraskeletal Ewing sarcoma with a germline pathogenic variant of SMARCA4 - Kang, Min-Chae; Kong, Sun-Young; Park, Sang-Yoon; Park, Seog-Yun; Lee, Eun-Gyeong; Yoo, Chong Woo; Kim, Yun Hwan; Kim, Hyeji; Choi, Wonyoung (Frontiers in Oncology, 2024)
SMARCA4 (BRG1) is a core unit of the SWI/SNF complex, regulating gene transcription through chromatin remodeling. Germline SMARCA4 variants have been reported to be associated with various malignancies. Here, we report the first case of extraskeletal Ewing sarcoma in a young female patient with a germline pathogenic variant of SMARCA4 (c.3546 + 1G>A), diagnosed with next generation sequencing (NGS). This alteration was also identified in her familial lineage, including her sister who was previously diagnosed with small cell carcinoma of the ovary, hypercalcemic type, a malignancy highly associated with SMARCA4 mutations. Despite undergoing radical surgery and receiving systemic treatments including VeIP (vinblastine, ifosfamide, cisplatin), and VDC (vincristine, doxorubicin, cyclophosphamide) regimens, the patient succumbed to death due to disease progression. With the implementation of NGS, we anticipate that more cases with SMARCA4 mutations will be diagnosed in the future. Further research is necessary to unveil therapeutic targets associated for this oncogenic alteration.